Uji Fitokimia, Toksisitas dan Aktivitas Antioksidan Fraksi n-heksan dan Etil Asetat terhadap Ekstrak Jahe Merah (Zingiber officinale var. amarum) - Alpina Nora Kaban; Daniel Tarigan; Chairul Saleh (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2016)
Has conducted research on the phytochemical test, toxicity test and test the antioxidant activity of the fraction of n-hexane and ethyl acetate to extract red ginger (Zingiber officinale amarum var.). The dried leaves weighing 382 grams, was macerated using methanol, filtered and concentrated by rotary evaporator. Then the total extract of red ginger in fractionation with n-hexane and ethyl acetate. Based on the test results of secondary metabolites phytochemical extracts of total red ginger (Zingiber officinale var amarum.) Are alkaloids, flavonoids, triterpenoids and phenolic. N-hexane fraction contains alkaloids, flavonoids, steroids, triterpenoids and phenolic. Ethyl acetate fractions contain alkaloids, flavonoids, triterpenoids and phenolic. Toxicity test showed the mortality rate of shrimp larvae Artemia salina Leach using Probit Analysis SAS (Statistical Analysis System) to determine the value of 50% Lethal Concentration (LC50), showed that the fraction of n-hexane toxicity with LC50 values of 63.8130 ppm; extracts of total was 71.0121 ppm and ethyl acetate was 3821.89 ppm. Test the antioxidant activity using DPPH free radical reduction in the spectrophotometer and IC50 values obtained on a total extract was 32.19 ppm; n-hexane was fraction 35.63 ppm; and ethyl acetate fraction was 25.69 ppm.